KOMPARASI PAJAK PERTAMBAHAN NILAI DI INDONESIA DENGAN GOODS AND SERVICES TAX DI SINGAPURA - Listia Aulia Indy (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to compare the Value Added Tax (VAT) system in Indonesia with the Goods and Services Tax (GST) in Singapore, focusing on rate structure, collection mechanisms, and their economic implications. The research method employed is a literature review using a descriptive-comparative approach. The analysis reveals that although both countries implement a value-added-based consumption tax, there are significant differences in terms of rates (Indonesia's VAT is 12% with a tax base based on other values, while Singapore's GST will be 9% by 2025), collection mechanisms, and implementation effectiveness. Singapore is considered more successful in managing its GST due to strong digitalization support and a relatively high level of taxpayer compliance. In contrast, Indonesia faces structural and institutional challenges that affect the efficiency of its VAT collection. The findings suggest the need for policy evaluation of Indonesia’s VAT system to improve its efficiency, technological adaptability, and contribution to enhancing national economic competitiveness.